Middle to late Pleistocene record of explosive volcanic eruptions in marine sediments offshore Kamchatka (Meiji Rise, NW Pacific). (18th December 2019) - Derkachev, Alexander N.; Gorbarenko, Sergey A.; Ponomareva, Vera V.; Portnyagin, Maxim V.; Malakhova, Galina I.; Liu, Yanguang
ABSTRACT: This paper presents the first detailed study of a late Pleistocene marine tephra sequence from the NW Pacific, downwind from the Kamchatka volcanic arc. Sediment core SO201‐2‐40, located on the Meiji Rise 400 km offshore the peninsula, includes 25 tephras deposited within the last 215 ka. Volcanic glass from the tephras was characterized using single‐shard electron microprobe analysis and laser ablation inductively coupled mass spectrometry. The age of tephras was derived from a new age model based on paleomagnetic and paleoclimate studies. Geochemical correlation of distal tephras to Kamchatkan pyroclastic deposits allowed the identification of tephras from the Karymsky, Gorely, Opala and Shiveluch eruptive centers. Three of these tephras were also correlated to other marine and terrestrial sites and hence are identified as the best markers for the north‐west Pacific region. These are an early Holocene tephra from the Karymsky caldera ( 8.7 ka) and two tephras falling into the Marine Isotope Stage (MIS) 6 glacial time: an MIS 6.4 tephra from Shiveluch ( 141 ka) and the MIS 6.5 Rauchua tephra ( 175 ka) from Karymsky. The data presented in this study can be used in paleovolcanological and paleoceanographic reconstructions.